Role of Efficient Human Resource Management in Managing Diversified Organizations - Minghua, Huang (Frontiers in Psychology, 2022)
As the world has turned into a global village, it has created many challenges for human resource departments regarding the management of a diverse workforce in satisfying the employees and creating a diverse yet safe environment for them that does not make them uncomfortable. The current study has investigated the effect of human resource practices on the diversity climate with the mediation of job satisfaction. The data has been collected from human resource personnel of multinationals in China with the help of 316 participants. The study deployed SEM analysis to analyze and measure the effect of training and development along with performance appraisal on the diversity climate. The findings of the study revealed that training and growth or development do not have an impact on the diversity climate, however, performance appraisal has a strong positive impact. Similarly, the mediating role of job satisfaction has been found to ensure the relationship of training and development and performance appraisal with the diversity climate. This study has provided certain implications for the HR managers of multinationals to ensure a secure diversity climate for a diverse workforce.